2020
DOI: 10.1097/pcc.0000000000002338
|View full text |Cite
|
Sign up to set email alerts
|

Shock Severity Modifies Associations Between RBC Transfusion in the First 48 Hours of Sepsis Onset and the Duration of Organ Dysfunction in Critically Ill Septic Children*

Abstract: Objective: To test the hypothesis that early RBC transfusion is associated with duration of organ dysfunction in critically ill septic children. Design: Secondary analysis of a single-center prospective observational study. Multivariable negative binomial regression was used to determine relationships between RBC transfusion within 48 hours of sepsis onset and number of days in 14 with organ dysfunction, or with multiple organ dysfunction syndrome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Additionally, our results showed that receipt of a RBC transfusion was also associated with a higher risk of a longer duration of MODS, an observation that was recently the subject of another secondary analysis of this data set [32]. We also found that the presence of baseline immune compromise was associated with fewer MODS days in patients with immunoparalysis.…”
Section: Discussionsupporting
confidence: 71%
“…Additionally, our results showed that receipt of a RBC transfusion was also associated with a higher risk of a longer duration of MODS, an observation that was recently the subject of another secondary analysis of this data set [32]. We also found that the presence of baseline immune compromise was associated with fewer MODS days in patients with immunoparalysis.…”
Section: Discussionsupporting
confidence: 71%
“…* * e C4 levels of the control group before and after intervention were obviously different (t � 10.183, P < 0.001). and amount of diet need to be controlled [17][18][19][20]. Food is provided according to the children's preferences to improve their interest in eating and increase their intake of energy and protein.…”
Section: Discussionmentioning
confidence: 99%
“…If such a heterogeneity of treatment effect exists, the overall net effect may show no difference between groups, but this net noneffect may not be informative for individual patients. In support of this hypothesis, our previous single center data in children with severe sepsis/septic shock suggest that hemodynamic measures, suggesting impaired ability to compensate (or sustain compensation) for anemia would likely identify children who benefit from RBC transfusion better than hemoglobin concentration alone (5). Understanding and evaluating patient-specific indications for RBC transfusion based on hemodynamic parameters and markers of the adequacy of oxygen delivery remains imperative to design more informative clinical trials of RBC transfusion strategies for children with shock.…”
Section: Discussionmentioning
confidence: 80%
“…The extent to which RBC transfusion contributes to organ dysfunction in critically ill children remains unclear. In our previous single-center study, early RBC transfusion was associated with longer durations of both single and multiple organ dysfunction in children with severe sepsis/septic shock, though these associations were modified by measures related to hemodynamics (vasoactive inotrope score and shock index) such that adverse effects related to RBC transfusion were greatest in those with the lowest shock severities (5). In a previous single-center observational study of critically ill children across multiple diagnoses, RBC transfusion was independently associated with the development of new or progressive MODS (aOR 3.85, 95% CI 2.4-6.2), accounting for PRISM III score, age, and the presence of congenital heart disease (8).…”
Section: Discussionmentioning
confidence: 92%